1993
DOI: 10.1159/000457540
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between Indomethacin-Induced Reduction in Neonatal Cerebral Blood Flow Velocity and Prostaglandin Production?

Abstract: Indomethacin lowers neonatal cerebral perfusion immediately after intravenous administration. It is important to elucidate whether this reduction is mediated by inhibition of production of prostaglandins, especially prostacyclin, which plays an important role in the autoregulation of the neonatal cerebral vascular bed. We studied changes in cerebral blood flow by serial measurements of temporal mean flow velocity in the anterior cerebral artery (TMFY-ACA), relative cerebral vascular resistance (R-cer), and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…They proposed that changes in gut perfusion associated with indomethacin may account for the increased incidence of necrotizing enterocolitis and perforations that are observed with its use. Finally, indomethacin compromises cerebral blood flow in the neonate [5][6][7][8][9][10][11][12][13][14][15][16]. Edwards et al [10] observed that indomethacintreated preterm infants displayed a sharp reduction in cerebral blood flow, oxygen delivery, blood volume and reactivity of blood volume to changes in arterial carbon dioxide as measured by near-infrared spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They proposed that changes in gut perfusion associated with indomethacin may account for the increased incidence of necrotizing enterocolitis and perforations that are observed with its use. Finally, indomethacin compromises cerebral blood flow in the neonate [5][6][7][8][9][10][11][12][13][14][15][16]. Edwards et al [10] observed that indomethacintreated preterm infants displayed a sharp reduction in cerebral blood flow, oxygen delivery, blood volume and reactivity of blood volume to changes in arterial carbon dioxide as measured by near-infrared spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…However, indomethacin also affects renal, gastrointestinal and cerebral perfusion [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and may lead to a significant incidence of complications as a result. Alternative and safer treatments would be preferable.…”
Section: Introductionmentioning
confidence: 99%
“…Esto ha sido evaluado en estudios clínicos realizados en niños prematuros por eco-Doppler 107,113,[229][230][231][232][233][234][235][236] , por NIRS (por sus siglas en inglés: Near Infra Red Spectroscopy) 144,[237][238][239] o por ambos métodos 238 , y también en animales neonatales 240,241 . Esencialmente, la administración de indometacina produce cambios en la hemodinámica y oxigenación cerebral que concuerdan con la disminución de la perfusión cerebral 113,144,[229][230][231][232][233][234][235][236][237][238][239] que persiste en el tiempo 234 . Los hallazgos son controvertidos, sin embargo, no lo son en cuanto al efecto diferencial de la administración en bolo frente a la infusión lenta 107,113,144,230 .…”
Section: ¿Efectos Diferentes De Indometacina E Ibuprofeno En El Cerebunclassified
“…El efecto de la indometacina en los vasos cerebrales parece ser directo 145 e independiente de potenciales cambios en el metabolismo de los prostanoides 235 . La administración precoz (< 12 h) de indometacina para el tratamiento del DAP de gran tamaño (> 1,6 mm) no produce a la hora de la administración cambios en el diámetro ductal ni en el flujo a la VCS.…”
Section: ¿Efectos Diferentes De Indometacina E Ibuprofeno En El Cerebunclassified
“…INDO administration produces substantial changes in cerebral hemodynamics immediately after its administration. This has been evaluated in clinical studies in premature infants by noninvasive techniques such as Doppler ultrasound 107,113,[229][230][231][232][233][234][235][236] , NIRS (Near Infra Red Spectroscopy) 144,[237][238][239] or combined modalities 238 and also in animal models 240,241 .…”
Section: Different Effects From Indo and Ibu In The Brain? Preventionmentioning
confidence: 99%